2018
DOI: 10.1097/meg.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

Infectious endocarditis in the case of cirrhosis: where do we stand?

Abstract: Bacterial infections are common in the case of cirrhosis and represent a major cause of morbidity and mortality. The most frequent infections are spontaneous bacterial peritonitis, urinary tract infection, and pneumonia, but few data on infectious endocarditis are available. Infectious endocarditis is a rare event, and diagnosis can be made at all stages of Child-Pugh classification. In the case of cirrhosis, the clinical features and bacterial ecology are similar to that of the general population (two males/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The factors related with liver function were consistently significant predictors of PVO patients’ survival (Table 3) (Fig. 2), and these results are in line with the results of other types of infection in patients with cirrhosis 39,40 . The multivariate analysis identified CTP class and MELD score as significant predictors of 30-day and 90-day mortality, respectively (Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…The factors related with liver function were consistently significant predictors of PVO patients’ survival (Table 3) (Fig. 2), and these results are in line with the results of other types of infection in patients with cirrhosis 39,40 . The multivariate analysis identified CTP class and MELD score as significant predictors of 30-day and 90-day mortality, respectively (Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…Gut translocation is postulated to be an important source of bacteremia in patients with ESLD due to reduced motility and increased permeability [3]. Prior studies have reported comparable microbiological results amongst patients with and without cirrhosis [17]. We observed streptococci to be the most common cause of infective endocarditis and Gram-negative bacteria to be less common in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 54%
“…In our study, ESLD patients with infective endocarditis have significantly higher in-hospital mortality as compared to patients without ESLD (OR 1.48, CI, 1.30-1.69). Perez de Isla [9] reported no significant difference in in-patient mortality; however, recently, Allaire et al [17] and Fernandez Guerrero et al [8] found significantly higher mortality in patients with cirrhosis. Decompensated liver disease and not liver cirrhosis was recently reported to be associated with mortality by Allaire et al, [7]; however, almost 90% of patients were decompensated at admission in that study.…”
Section: Discussionmentioning
confidence: 97%
“…Preexisting liver disease predisposes to infective endocarditis 183 and influences prognosis and mortality: particularly liver cirrhosis is much more prevalent in nonsurvivors of infective endocarditis. 60,184 However, a large cohort study showed that the degree of preexisting liver disease has important prognostic consequences: patients with Child Pugh A liver cirrhosis had comparable outcomes to noncirrhotic patients, both with surgical and conservative treatment. Only in stages B and C was the outcome significantly worse.…”
Section: Liver Dysfunction and Splenic Complicationsmentioning
confidence: 99%